Diffuse astrocytoma, IDH-wildtype: a dissolving diagnosis - Hasselblatt, Martin; Reuss, David; Deimling, Andreas von (Journal of neuropathology and experimental neurology, 2018)
Abstract. The histological and molecular features and even the mere existence of diffuse astrocytoma, IDH-wildtype, remain unclear. We therefore examined 212 d